Experimental Validation of the Finite Element Modelling of Pinhão Bridge - Filipe Magalhães (2006)
The Pinhão Bridge is a Portuguese metallic roadway bridge constructed in 1906 over the Douro river, whose state of degradation requires the development of rehabilitation works (Figure 1). In this context, an ambient vibration test of the bridge was recently performed. The collected data was processed using the Peak-Picking method that allowed the identification of the most relevant natural frequencies (Figure 2) and mode shapes. The experimental identified modal parameters were used to improve the numerical model developed by the consultancy office responsible for the rehabilitation design. The updated finite element model provides very well correlated natural frequencies and vibration modes with regard to the corresponding experimental estimates (Figure 3).